2013
DOI: 10.1007/s00586-013-3059-z
|View full text |Cite
|
Sign up to set email alerts
|

A SNP in the 5′UTR of GDF5 is associated with susceptibility to symptomatic lumbar disc herniation in the Chinese Han population

Abstract: Our results suggested that the GDF5 polymorphism is associated with a susceptibility to symptomatic lumbar disc herniation in the Chinese Han population and type II collagen in the nucleus pulposus may be a key factor in susceptibility to symptomatic lumbar disc herniation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…LDH is considered to be a disease caused by the multifactorial interactions (Lin et al, 2013;Mu, Ge, Zuo, Chen, & Huang, 2014). To better understand the complex pathogenesis of LDH, we explore the association of GPC6 polymorphisms with LDH risk in the Han Chinese population for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…LDH is considered to be a disease caused by the multifactorial interactions (Lin et al, 2013;Mu, Ge, Zuo, Chen, & Huang, 2014). To better understand the complex pathogenesis of LDH, we explore the association of GPC6 polymorphisms with LDH risk in the Han Chinese population for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…A single point mutation of a nucleotide may affect many regulatory steps involved in protein synthesis. From previous studies, SNPs in the 5'-UTR have been found to cause some diseases, such as the GDF5 gene associated with osteoarthritis (Mu et al, 2014) and the HOPX gene related to syncope in hypertrophic cardiomyopathy patients (Gulec et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of current research, trauma, environmental and genetic factors are considered to be the main causes of disease. However the precise etiology and pathogenesis underlying of LDH are complex and still poorly understood (Mu, Ge, Zuo, Chen, & Huang, ).…”
Section: Introductionmentioning
confidence: 99%